Periodontitis in children, adolescent and young adults. The changing concepts: 2. Aetiology and treatment - Yusof, W.Z. (1988)
Early-onset periodontitis in children, teenagers and young adults is quite rare. This form of periodontitis progresses very rapidly and cause massive destruction to the periodontium. Various names have been given to this condition since it was first recognised in the 1920s. Through time the nomenclature changed from one to the other. Currently 3 forms of early-onset periodontitis are recognised--i.e. prepubertal periodontitis (PPP), localised juvenile periodontitis (LJP) and rapidly progressive periodontitis (RPP). The clinical features of juvenile periodontitis as it was first described together with that of the present 3 clinical entities mentioned above are presented. Concepts on the aetiology of the disease have also changed through time, and include degenerative process, bacterial infection, defects in the host defense system and heredity. Current thought is that there is an interplay of most of these factors in pathogenesis of the disease. Treatment modalities changed too. At the moment, comprehensive periodontal therapy with meticulous oral hygiene measures seem to be the treatment of choice. Concurrently, systemic tetracycline administration might have some added benefits.